Strategic Norm Replacement in Thailand - Anchalee Rüland (Norms in Conflict, 2022)
Following the analysis of Indonesia’s response to norm conflict, this chapter assesses the response of successive Thai governments to situations of norm conflict in neighboring Myanmar. In doing so, it illustrates strategic norm replacement as a response category to norm conflict. The chapter demonstrates that in the three cases of human rights violation in Myanmar, successive Thai governments consistently prioritized the noninterference norm over human rights protection. It shows that in view of strong conflicting expectations toward action articulated at the domestic and international levels, the government justified its response by framing noninterference as the only appropriate norm to regulate